The Distribution of Welfare: Inequality, Earnings Capacity, and Household Production in a Comparative Perspective - Peter Saunders; Inge O'Connor; Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1994)
Cross-national comparisons of earnings inequality can be misleading when unemployment rates and rate of female labor force participation differ across countries. This is because such comparisons implicitly place zero values on underutilized labor market activity and domestic labor. This paper approaches this problem by using an earnings capacity technique developed by Irwin Garfinkel and Robert Haveman, an extension of Gary Becker's full-income concept.
Keywords: 330